Type specimens of the world’s hard tick species (Acari: Ixodida: Ixodidae): collection data and depositories for all valid names and the current status of invalid names - Robbins, Richard G.; Nava, Santiago; Ronai, Isobel; Chong, Kailyn L.; Guglielmone, Alberto (Magnolia Press, 2025)
The hard tick family Ixodidae currently comprises 786 species worldwide, plus many invalid names, synonyms, and names that are incertae sedis, nomina nuda, or nomina dubia, as well as suppressed names. For both the valid and invalid tick species, we provide critically important information on their type specimens, including depositories, type localities and type hosts. Additionally, we include the current taxonomic status of 226 invalid names where type information is lacking. This compilation of information for the world’s ixodid type specimens should facilitate access to them, thereby enhancing opportunities to compare closely related species and resolve some of the many taxonomic problems currently confronting both tick specialists and public health professionals. The literature search for this study ended on May 15, 2024.